Preparation process of anti-corrosion and anti-scale device

By preparing precious metal alloy chips with consistent orientation columnar crystal structures and installing them in the pipeline, the existing anti-corrosion and scale prevention methods are solved, and the existing anti-corrosion and scale prevention methods are achieved is achieved, and the operating cost is reduced.

CN119876657APending Publication Date: 2025-04-25SHANXI BOGE HYDRAULIC MACHINERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510109248.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing anti-corrosion and anti-scaling methods have problems such as adverse impact on the environment or high production costs.

Method used

Using a preparation process of anti-corrosion and scale anti-attack, the alloy powder is formed by selecting more than seven precious metal elements with different electronegative properties, and melting it into an alloy ingot with a consistent oriented columnar crystal structure under vacuum or inert gas protection. After heat treatment and mechanical processing, the orifice plate blade-type scale-resistant alloy chip is formed, and installed in the pipeline to make it in contact with the fluid.

Benefits of technology

Release free electrons through the alloy chip to change the electrostatic potential of water, achieve the polarization effect of the fluid, prevent scaling and descaling, and at the same time generate a protective film to prevent pipeline corrosion, significantly reduce the operating cost of water treatment and be more environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876657A_ABST
    Figure CN119876657A_ABST
Patent Text Reader

Abstract

The invention relates to the field of anti-scale device preparation, and discloses a preparation process of an anti-corrosion anti-scale device, which comprises the following steps: S1, selecting more than seven noble metal elements with different electronegativity: 5%-10% of silver (Ag), 10%-15% of copper (Cu), 15%-20% of nickel (Ni), 5%-10% of zinc (Zn), 20%-25% of titanium (Ti), 10%-15% of chromium (Cr) and 5%-10% of platinum (Pt); s2, metal elements are mixed and processed, and the precious metal elements in the S1 are evenly mixed to form alloy powder; and S3, smelting and ingot casting are conducted, specifically, under vacuum or inert gas protection, alloy powder is smelted at the temperature of 1200-1400 DEG C, and the smelting time is 2 hours. According to the invention, the alloy chip releases free electrons to change the electrostatic potential of water, no chemical agent is needed, the problem of secondary pollution of the agent is avoided, the operation cost of water treatment is obviously reduced, and the water treatment device is more environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of anti-scaling device preparation, and in particular to a preparation process of an anti-corrosion and anti-scaling device. Background Art

[0002] In the field of water treatment, scaling and corrosion are common problems that seriously affect the operating efficiency and life of industrial equipment. Traditional anti-corrosion and anti-scaling methods mainly include chemical treatment, physical treatment and biological treatment. Chemical treatment methods prevent scaling and corrosion by adding chemical agents such as corrosion inhibitors and scale inhibitors to water. However, this method is not only costly, but also has adverse effects on the environment and human health in the long term.

[0003] Physical treatment methods change the physical properties of water by mechanical or electromagnetic means, such as ultrasonic descaling and magnetization treatment. Although these methods are environmentally friendly, their effects are unstable, and the equipment is complex, making them difficult to apply on a large scale. Biological treatment methods prevent scaling and corrosion through the formation of biofilms, but they have high requirements for water quality and high maintenance costs. Summary of the invention

[0004] In order to make up for the above deficiencies, the present invention provides a preparation process of an anti-corrosion and anti-scaling device, aiming to improve the problems of "adverse effects on the environment or high production costs" mentioned in the prior art.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme: a preparation process of an anti-corrosion and anti-scaling device, comprising the following steps:

[0006] S1: Select precious metal elements

[0007] Select seven or more precious metal elements with different electronegativity, and the proportion of each element is as follows: silver (Ag) 5% to 10%, copper (Cu) 10% to 15%, nickel (Ni) 15% to 20%, zinc (Zn) 5% to 10%, titanium (Ti) 20% to 25%, chromium (Cr) 10% to 15%, platinum (Pt) 5% to 10%;

[0008] S2: Mixing metal elements

[0009] Mix the precious metal elements in S1 evenly to form alloy powder;

[0010] S3: Melting and ingot making

[0011] Under vacuum or inert gas protection, the alloy powder is melted at a temperature of 1200-1400°C for 2 hours, and then the molten alloy liquid is poured into an ingot mold for slow cooling and directionally solidification to form an alloy ingot with a columnar crystal structure with consistent orientation;

[0012] S4: Heat treatment

[0013] Normalizing the ingot material at a temperature of 800-900°C for 1-2 hours, then quenching the ingot material at a temperature of 1000-1100°C for 0.5-1 hour, and finally tempering the ingot material at a temperature of 400-500°C for 1-2 hours;

[0014] S5: Machining

[0015] The heat-treated ingot material is made into a scale-inhibiting alloy chip with a diameter of 20-50 mm and a thickness of 5-10 mm;

[0016] S6: Material installation and use

[0017] Install the anti-scaling alloy chip in the pipeline so that it comes into contact with the fluid.

[0018] As a further description of the above technical solution:

[0019] The anti-scaling alloy chip structure is designed in the form of an orifice plate blade and uses a spiral stacking installation method to maximize the contact area of ​​the fluid. The orifice plate blade type anti-scaling alloy chip has a pore diameter of 0.5-2.0 mm, a pore spacing of 1.0-3.0 mm, a blade spacing of 2.0-4.0 mm, and a blade thickness of 0.5-1.0 mm.

[0020] As a further description of the above technical solution:

[0021] The heat treatment step in S4 also includes annealing at a temperature of 600-700° C. for 1-2 hours to further optimize the crystal structure and mechanical properties of the material.

[0022] As a further description of the above technical solution:

[0023] The material of the orifice plate blade type anti-scaling alloy chip contains nano catalysts inside, and the nano catalysts can further promote the release of free electrons and improve the anti-scaling and anti-corrosion effects of the material.

[0024] As a further description of the above technical solution:

[0025] The surface of the orifice plate blade type anti-scaling alloy chip is subjected to surface modification treatment, such as electroplating or spraying, to improve its corrosion resistance and electrical conductivity.

[0026] As a further description of the above technical solution:

[0027] The flow rate of the fluid when passing through the chip is 0.2-3 m / s, so as to ensure that the fluid produces the best polarization effect when passing through the chip.

[0028] As a further description of the above technical solution:

[0029] The orifice plate blade type anti-scaling alloy chip releases free electrons in the fluid, changes the electrostatic potential of the fluid, and causes the fluid to produce a polarization effect. The anions and cations in the polarized fluid are not easy to combine to form scale, and the formed scale blocks can be gradually dissolved and shed, effectively preventing scaling and descaling.

[0030] As a further description of the above technical solution:

[0031] The hardness range of the fluid medium needs to be less than or equal to 1500 mg / L, the mineralization range needs to be less than or equal to 350000 mg / L, the pH value range is 5.0-9.0, and the steady-state current range is 30 μA.

[0032] As a further description of the above technical solution:

[0033] The orifice plate blade type anti-scaling alloy chip has an operating temperature range of -20°C to 100°C and is suitable for water treatment systems in various working environments.

[0034] As a further description of the above technical solution:

[0035] The service life of the orifice plate blade type anti-scaling alloy chip is 3 to 5 years. By regularly replacing the chip, the long-term stable operation of the equipment and the efficient anti-scaling and anti-corrosion effect are ensured.

[0036] The present invention has the following beneficial effects:

[0037] 1. In the present invention, the electrostatic potential of water is changed by releasing free electrons through the alloy chip, and no chemical agents are required, thus avoiding the problem of secondary pollution of agents. At the same time, the operating cost of water treatment is significantly reduced, which is more environmentally friendly. In addition, the orifice blade type anti-scaling alloy chip of the present invention can not only prevent scale, but also prevent pipeline corrosion by generating a protective film. The dipoles in the polarized fluid and the metal surface of the pipe wall produce a wall effect to form a layer of scale-forming ion coupling, which separates the pipe wall metal from the fluid system, thereby effectively preventing the occurrence of corrosion. The experimental results show that there is no obvious corrosion on the inner wall of the pipe using the chip, which further verifies the anti-corrosion effect of the chip.

[0038] 2. In the present invention, by simple mechanical installation in the pipeline, free electrons can be continuously released to form a stable polarization effect, thereby maintaining good anti-scaling and anti-corrosion effects under various working environments. The equipment has a simple structure, is easy to install and maintain, and is suitable for large-scale applications.

[0039] 3. In the present invention, through multiple embodiment experiments, it is concluded that it can be applied to a variety of water quality conditions, including tap water and groundwater with different hardness. The experimental results show that good anti-scaling and anti-corrosion effects are exhibited under the conditions of tap water with a hardness of 1500 mg / L and tap water with a mineralization of 300000 mg / L. The service life of the chip is 3 to 5 years. By regularly replacing the chip, the long-term stable operation and efficient anti-scaling and anti-corrosion effects of the equipment can be ensured, and maintenance is relatively simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a process flow diagram of a preparation process of an anti-corrosion and anti-scaling device in the present invention;

[0041] Figure 2 The present invention is a schematic diagram showing the morphology of a complete 3D columnar crystal as shown by a cross-section SEM electron microscope image of the 3D columnar crystal;

[0042] Figure 3 Schematic diagram of the effect of microcurrent on the crystal structure of scale salt in the present invention. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Embodiment 1

[0045] Reference Figure 1 - Figure 3 The present invention provides a preparation process of an anti-corrosion and anti-scaling device, comprising the following steps:

[0046] S1: Select precious metal elements

[0047] More than seven precious metal elements with different electronegativity are selected, and the proportion of each element is as follows: silver (Ag) 7%, copper (Cu) 12%, nickel (Ni) 18%, zinc (Zn) 7%, titanium (Ti) 22%, chromium (Cr) 11%, platinum (Pt) 6%, among which silver (Ag) has good electrical conductivity and antibacterial properties, and can significantly improve the free electron release ability of the material, copper (Cu) can form a good alloy structure with silver, improve the mechanical strength and corrosion resistance of the material, nickel (Ni) enhances the magnetism of the material and promotes the polarization effect of the fluid medium, zinc (Zn) has good oxidation resistance and prevents the material from being oxidized during use, titanium (Ti) improves the hardness and high temperature resistance of the material, chromium (Cr) enhances the corrosion resistance of the material and prevents corrosion under complex water conditions, and platinum (Pt) improves the catalytic activity of the material and promotes the release of free electrons;

[0048] S2: Mixing metal elements

[0049] Mix the precious metal elements in S1 evenly to form alloy powder;

[0050] S3: Melting and ingot making

[0051] Under vacuum or inert gas protection, the alloy powder is melted at 1300°C for 2 hours, and then the molten alloy liquid is poured into an ingot mold for slow cooling and directionally solidification to form an alloy ingot with a columnar crystal structure with consistent orientation. The 3D columnar crystal cross-section SEM electron microscope image shows that it has a complete 3D columnar crystal morphology, such as Figure 2 As shown;

[0052] S4: Heat treatment

[0053] The ingot material is normalized at 850°C for 1 hour, then quenched at 1050°C for 0.5 hour, and finally tempered at 450°C for 1 hour, and annealed at 650°C for 1.5 hours to further optimize the crystal structure and mechanical properties of the material;

[0054] S5: Machining

[0055] The heat-treated ingot material is made into an anti-scaling alloy chip with a diameter of 30 mm and a thickness of 8 mm. Specifically, the anti-scaling alloy chip structure is designed in the form of a perforated plate blade, and a spiral stacking installation method is adopted to maximize the contact area of ​​the fluid. The aperture of the orifice plate blade type anti-scaling alloy chip is 1.0 mm, the hole spacing is 2.0 mm, the blade spacing is 3.0 mm, and the blade thickness is 0.8 mm. The material of the orifice plate blade type anti-scaling alloy chip contains nanocatalysts, which can further promote the release of free electrons and improve the anti-scaling and anti-corrosion effects of the material. The surface of the orifice plate blade type anti-scaling alloy chip is treated with a surface Surface modification treatment, such as electroplating or spraying, to improve its corrosion resistance and conductivity. More specifically, the operating temperature range of the orifice blade type anti-scaling alloy chip is -20℃ to 100℃, which is suitable for water treatment systems under various working environments. The service life of the orifice blade type anti-scaling alloy chip is 3 to 5 years. By regularly replacing the chip, the long-term stable operation and efficient anti-scaling and anti-corrosion effect of the equipment are ensured. The hardness range of the fluid medium needs to be less than or equal to 1500mg / L, the mineralization range needs to be less than or equal to 350000mg / L, the pH range is 7.0, and the steady-state current range is 30μA. The effect of microcurrent on the crystal structure of scale salt is as follows: Figure 3 As shown;

[0056] S6: Material installation and use

[0057] The anti-scaling alloy chip is installed in the pipeline to make it contact with the fluid. The flow rate of the fluid passing through the chip is 0.2-3m / s to ensure that the fluid produces the best polarization effect when passing through the chip. The orifice plate blade type anti-scaling alloy chip releases free electrons in the fluid, changes the electrostatic potential of the fluid, and causes the fluid to produce a polarization effect. The anions and cations in the polarized fluid are not easy to combine to form scale, and the formed scale blocks can be gradually dissolved and removed, effectively preventing scaling and descaling. The polarization effect produced by the orifice plate blade type anti-scaling alloy chip in the fluid can cause the dipole to have a wall effect with the metal surface of the pipe wall, so that a certain thickness of scale-forming ion coupling is deposited on the metal surface of the pipe wall, forming a protective film to separate the pipe wall metal from the fluid system, thereby achieving an anti-corrosion effect.

[0058] Experimental results:

[0059] Change of electrostatic potential: the initial electrostatic potential is 600mV, and the electrostatic potential after passing through the chip is 200mV; scale inhibition effect: the scale layer thickness of the pipeline without chip is 0.5mm, the scale layer thickness of the pipeline with chip is 0.05mm, and the scale inhibition rate is 95%.

[0060] Anti-corrosion effect: The inner wall of the pipe without the chip is obviously corroded, with a corrosion depth of 0.1 mm; the inner wall of the pipe with the chip has no obvious corrosion, and only a thin protective film is formed on the surface

[0061] Embodiment 2

[0062] Experimental materials: silver (Ag) 8%, copper (Cu) 13%, nickel (Ni) 17%, zinc (Zn) 6%, titanium (Ti) 23%, chromium (Cr) 12%, platinum (Pt) 5%, tin (Sn) 2%, and iron (Fe) 2%.

[0063] Experimental steps:

[0064] Element mixing: The above-mentioned precious metal elements and a small amount of tin (Sn) and iron (Fe) are uniformly mixed in a predetermined ratio to form an alloy powder.

[0065] Melting and ingot casting: The alloy powder is melted in a melting furnace under the protection of inert gas, the melting temperature is controlled to be 1350℃, and the melting time is 2 hours. The smelted alloy liquid is poured into an ingot casting mold, and slowly cooled and directionally solidified to form an alloy ingot with a columnar crystal structure with consistent orientation.

[0066] Heat treatment: normalize the ingot material at 820°C for 1.5 hours; quench at 1080°C for 35 minutes; temper at 480°C for 1.5 hours, and anneal at 650°C for 1.5 hours.

[0067] Machining: The heat-treated ingot material is cut and polished to make a 35 mm diameter and 7 mm thick orifice blade type anti-scaling alloy chip. The chip surface is designed with a orifice plate with a hole diameter of 1.5 mm and a hole spacing of 2.5 mm. The side is designed with spiral blades with a blade spacing of 3.5 mm and a blade thickness of 0.7 mm.

[0068] Fluid test: The prepared anti-scaling alloy chip was installed in a 304 stainless steel pipe and tested using groundwater with a hardness of 1200 mg / L. During the experiment, the flow rate was controlled at 2.0 m / s, and the static potential change of the fluid, the anti-scaling rate, and the corrosion of the pipe were monitored.

[0069] Experimental results:

[0070] Electrostatic potential change: The initial electrostatic potential is 700mV, and the electrostatic potential after passing through the chip is 250mV.

[0071] Scale inhibition effect: The scale layer thickness of the pipe without chip is 0.6 mm, the scale layer thickness of the pipe with chip is 0.06 mm, and the scale inhibition rate is 90%.

[0072] Anti-corrosion effect: The inner wall of the pipe without the chip showed obvious corrosion, with a corrosion depth of 0.15 mm; the inner wall of the pipe with the chip had no obvious corrosion, and only a thin protective film was formed on the surface.

[0073] Embodiment 3

[0074] Experimental materials: silver (Ag) 6%, copper (Cu) 14%, nickel (Ni) 16%, zinc (Zn) 8%, titanium (Ti) 24%, chromium (Cr) 13%, platinum (Pt) 7%, iron (Fe) 3%.

[0075] Experimental steps:

[0076] Element mixing: The above-mentioned precious metal elements and a small amount of iron (Fe) are uniformly mixed in a predetermined ratio to form alloy powder.

[0077] Melting and ingot casting: The alloy powder is melted in a melting furnace under the protection of inert gas, the melting temperature is controlled to be 1320℃, and the melting time is 2 hours. The smelted alloy liquid is poured into an ingot casting mold, and slowly cooled and directionally solidified to form an alloy ingot with a columnar crystal structure with consistent orientation.

[0078] Heat treatment: normalize the ingot material at 830°C for 1.2 hours; quench at 1060°C for 30 minutes; temper at 470°C for 1.2 hours, and anneal at 650°C for 1.5 hours.

[0079] Machining: The heat-treated ingot material is cut and polished to produce a 40 mm diameter, 6 mm thick orifice plate blade type anti-scaling alloy chip. The chip surface is designed with an orifice plate with an aperture of 1.2 mm and a hole spacing of 1.8 mm; the side is designed with spiral blades with a blade spacing of 3.0 mm and a blade thickness of 0.6 mm.

[0080] Fluid test: The prepared anti-scaling alloy chip was installed in a 304 stainless steel pipe and tested using tap water with a mineralization of 300,000 mg / L. During the experiment, the flow rate was controlled at 1.8 m / s, and the static potential change of the fluid, the anti-scaling rate, and the corrosion of the pipe were monitored.

[0081] Experimental results:

[0082] Electrostatic potential change: The initial electrostatic potential is 650mV, and the electrostatic potential after passing through the chip is 220mV.

[0083] Scale inhibition effect: The scale layer thickness of the pipe without the chip is 0.7 mm, the scale layer thickness of the pipe with the chip is 0.07 mm, and the scale inhibition rate is 90%.

[0084] Anti-corrosion effect: The inner wall of the pipe without the chip showed obvious corrosion, with a corrosion depth of 0.18 mm; the inner wall of the pipe with the chip had no obvious corrosion, and only a thin protective film was formed on the surface.

[0085] The following experimental results are obtained and presented in a table:

[0086]

[0087]

[0088] Comprehensive experimental results:

[0089] Example 1: Under the condition of tap water with a hardness of 1500 mg / L, the scale inhibition effect is the best (95%), and it is suitable for use in fluids with lower hardness.

[0090] Example 2: Under the condition of groundwater with a hardness of 1200 mg / L, the electrostatic potential change and anti-corrosion effect are optimal, and it is suitable for use in groundwater treatment systems.

[0091] Example 3: Under the condition of tap water with a mineralization degree of 300000 mg / L, the scale inhibition effect and the anti-corrosion effect are both good, and it is suitable for use in fluids with high mineralization degree.

[0092] Finally, it should be noted that the above are only preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A preparation process of an anti-corrosion and anti-scaling device, characterized in that: The following steps are involved: S1: Select precious metal elements Select seven or more precious metal elements with different electronegativity, and the proportion of each element is as follows: silver (Ag) 5% to 10%, copper (Cu) 10% to 15%, nickel (Ni) 15% to 20%, zinc (Zn) 5% to 10%, titanium (Ti) 20% to 25%, chromium (Cr) 10% to 15%, platinum (Pt) 5% to 10%; S2: Mixing metal elements Mix the precious metal elements in S1 evenly to form alloy powder; S3: Melting and ingot making Under vacuum or inert gas protection, the alloy powder is melted at a temperature of 1200-1400°C for 2 hours, and then the molten alloy liquid is poured into an ingot mold for slow cooling and directionally solidification to form an alloy ingot with a columnar crystal structure with consistent orientation; S4: Heat treatment Normalizing the ingot material at a temperature of 800-900°C for 1-2 hours, then quenching the ingot material at a temperature of 1000-1100°C for 0.5-1 hour, and finally tempering the ingot material at a temperature of 400-500°C for 1-2 hours; S5: Machining The heat-treated ingot material is made into a scale-inhibiting alloy chip with a diameter of 20-50 mm and a thickness of 5-10 mm; S6: Material installation and use Install the anti-scaling alloy chip in the pipeline so that it comes into contact with the fluid.

2. The preparation process of the anti-corrosion and anti-scaling device according to claim 1, characterized in that: The anti-scaling alloy chip structure is designed in the form of an orifice plate blade and uses a spiral stacking installation method to maximize the contact area of ​​the fluid. The orifice plate blade type anti-scaling alloy chip has a pore diameter of 0.5-2.0 mm, a pore spacing of 1.0-3.0 mm, a blade spacing of 2.0-4.0 mm, and a blade thickness of 0.5-1.0 mm.

3. The preparation process of the anti-corrosion and anti-scaling device according to claim 1, characterized in that: The heat treatment step in S4 also includes annealing at a temperature of 600-700° C. for 1-2 hours to further optimize the crystal structure and mechanical properties of the material.

4. The preparation process of the anti-corrosion and anti-scaling device according to claim 1, characterized in that: The material of the orifice plate blade type anti-scaling alloy chip contains nano catalysts inside, and the nano catalysts can further promote the release of free electrons and improve the anti-scaling and anti-corrosion effects of the material.

5. The preparation process of the anti-corrosion and anti-scaling device according to claim 1, characterized in that: The surface of the orifice plate blade type anti-scaling alloy chip is subjected to surface modification treatment, such as electroplating or spraying, to improve its corrosion resistance and electrical conductivity.

6. The preparation process of the anti-corrosion and anti-scaling device according to claim 2, characterized in that: The flow rate of the fluid when passing through the chip is 0.2-3 m / s, so as to ensure that the fluid produces the best polarization effect when passing through the chip.

7. The preparation process of the anti-corrosion and anti-scaling device according to claim 1, characterized in that: The orifice plate blade type anti-scaling alloy chip releases free electrons in the fluid, changes the electrostatic potential of the fluid, and causes the fluid to produce a polarization effect. The anions and cations in the polarized fluid are not easy to combine to form scale, and the formed scale blocks can be gradually dissolved and shed, effectively preventing scaling and descaling.

8. The preparation process of the anti-corrosion and anti-scaling device according to claim 1, characterized in that: The hardness range of the fluid medium needs to be less than or equal to 1500 mg / L, the mineralization range needs to be less than or equal to 350000 mg / L, the pH value range is 5.0-9.0, and the steady-state current range is 30 μA.

9. The preparation process of the anti-corrosion and anti-scaling device according to claim 1, characterized in that: The orifice plate blade type anti-scaling alloy chip has an operating temperature range of -20°C to 100°C and is suitable for water treatment systems in various working environments.

10. The preparation process of the anti-corrosion and anti-scaling device according to claim 1, characterized in that: The service life of the orifice plate blade type anti-scaling alloy chip is 3 to 5 years. By regularly replacing the chip, the long-term stable operation of the equipment and the efficient anti-scaling and anti-corrosion effect are ensured.